2019
DOI: 10.4018/978-1-5225-7567-2.ch005
|View full text |Cite
|
Sign up to set email alerts
|

“I Found Myself Retweeting”

Abstract: This chapter describes a mixed-method, multiple case study that examined ways in which synchronous educational Twitter chats were used, first, to enhance graduate and undergraduate university student learning, second, to build professional networks, and third, to provide a loosely regulated means to achieving self-determined professional development goals. Findings suggest that while difficult at the onset, participation in Twitter educational chats was an enhancement to students' overall course learning exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Researchers have also examined how different educational groups use Twitter chats as a method of professional learning. Recently, multiple studies have focused on preservice educators' participation in Twitter chats as a beneficial form of professional learning (Carpenter & Morrison, 2018;Delello & Consalvo, 2019;Krutka, 2014;Mullins & Hicks, 2019;Riech, Levinson, & Johnston, 2011). Adjapong et al (2018) found that educational participants who took part in a #HipHopEd Twitter chat found a sense of belonging within the chat community and reported that the professional learning they engaged in as part of these chats had an impact on their instructional practice; additionally, a majority of participants self-reported that #HipHopEd chat participation "impacted their practice by specifically encouraging them to be more engaging educators, possibly by gaining tools that supported the teaching to the specific needs of their students" (p. 34).…”
Section: Twitter As a Platform For Professional Learningmentioning
confidence: 99%
“…Researchers have also examined how different educational groups use Twitter chats as a method of professional learning. Recently, multiple studies have focused on preservice educators' participation in Twitter chats as a beneficial form of professional learning (Carpenter & Morrison, 2018;Delello & Consalvo, 2019;Krutka, 2014;Mullins & Hicks, 2019;Riech, Levinson, & Johnston, 2011). Adjapong et al (2018) found that educational participants who took part in a #HipHopEd Twitter chat found a sense of belonging within the chat community and reported that the professional learning they engaged in as part of these chats had an impact on their instructional practice; additionally, a majority of participants self-reported that #HipHopEd chat participation "impacted their practice by specifically encouraging them to be more engaging educators, possibly by gaining tools that supported the teaching to the specific needs of their students" (p. 34).…”
Section: Twitter As a Platform For Professional Learningmentioning
confidence: 99%